Sleep deprivation impairs inhibitory control during wakefulness in adult sleepwalkers. (19th June 2015) - Labelle, Marc‐Antoine; Dang‐Vu, Thien Thanh; Petit, Dominique; Desautels, Alex; Montplaisir, Jacques; Zadra, Antonio
Summary: Sleepwalkers often complain of excessive daytime somnolence. Although excessive daytime somnolence has been associated with cognitive impairment in several sleep disorders, very few data exist concerning sleepwalking. This study aimed to investigate daytime cognitive functioning in adults diagnosed with idiopathic sleepwalking. Fifteen sleepwalkers and 15 matched controls were administered the Continuous Performance Test and Stroop Colour‐Word Test in the morning after an overnight polysomnographic assessment. Participants were tested a week later on the same neuropsychological battery, but after 25 h of sleep deprivation, a procedure known to precipitate sleepwalking episodes during subsequent recovery sleep. There were no significant differences between sleepwalkers and controls on any of the cognitive tests administered under normal waking conditions. Testing following sleep deprivation revealed significant impairment in sleepwalkers' executive functions related to inhibitory control, as they made more errors than controls on the Stroop Colour‐Word Test and more commission errors on the Continuous Performance Test. Sleepwalkers' scores on measures of executive functions were not associated with self‐reported sleepiness or indices of sleep fragmentation from baseline polysomnographic recordings. The results support the idea that sleepwalking involves daytime consequences and suggest that these may also include cognitive impairments in the form of disrupted inhibitory control following sleep deprivation. These disruptions may represent a daytime expression of sleepwalking's pathophysiological mechanisms.